Damage of hydroelectric power plant trash-racks due to fluid-dynamic exciting frequencies - Nascimento, L. P. [UNESP]; Silva, J. B.C. [UNESP]; Di Giunta, V. [UNESP] (My University, 2006)
This work is concerned with damages of trash-racks of hydroelectric power plants excited by the flow passing around them, and with the analysis of virtual mass effect on the natural frequencies and mode shapes of the trash-racks. A model for simulation of the flow passing through a big trash-rack regarding the effect of its obstruction due to aquatic plants accumulation is presented. The vortex shedding frequencies has been determined for several operating conditions. A finite element model has also been developed for analysis of the modal characteristics of the trash-rack. The fluid-structure interaction effect or hydroelastic vibration structure has been included in this model and the modal characteristics have been determined regarding the structure immersed in water and in air. Furthermore, the natural frequencies and vortex shedding frequency approaches have indicated that the trash-rack damages are probably due to operating at resonant conditions.
Keywords: Flow simulation; Fluid-structure; Hydroelectric machine; Modeling; Trash-rack